The significance of property sector diversification and regional diversification for property investment - Sipan, Ibrahim @ Atan; Mohd. Ali, Hishamuddin; Cheok, Bee Khim (2005)
We buy real estate for one of two reasons. The first reason is to provide a shelter for us or to place our businesses. The second reason is an investment for income stream through rentals. Residential property for many years has been the money-making portfolio for most investors surveyed (Atsir, 1993). Therefore, other than commercial and industrial properties, residential property investment could also provide return to investors by rental growth and capital appreciation. Portfolio managers and investors are often making investment decision either diversify their investment through geographic or property sector. The Malaysian House Price Index is used and was obtained from National Property Information Centre (NaPIC) at Valuation and Property Services Department (VPSD). The study areas include Kuala Lumpur, Selangor, Johor and Pulau Pinang from year 1994 until year 2003 to find out whether diversification within a region by property sector is better than diversification within property sector by region or vice versa. The correlation coefficient analysis is used to compare the diversification by the average correlation for property sector and regional. The efficient frontier then was formed to determine the performance of each property and region. The finding of this study shows the regional diversification is more significance than property sector diversification. Keywords: Diversification, Housing, Property Investment.